Is There Room at the Bottom for CSR? Corporate Social Responsibility and Nanotechnology in the UK - Groves, Chris; Frater, Lori; Lee, Robert; Stokes, Elen (2011)
Nanotechnologies are enabling technologies which rely on the manipulation of matter on the scale of billionths of a metre. It has been argued that scientific uncertainties surrounding nanotechnologies and the inability of regulatory agencies to keep up with industry developments mean that voluntary regulation will play a part in the development of nanotechnologies. The development of technological applications based on nanoscale science is now increasingly seen as a potential test case for new models of regulation based on future-oriented responsibility, lifecycle risk management, and upstream public engagement. This article outlines findings from a project undertaken in 2008–2009 for the UK Government’s Department of Environment, Food and Rural Affairs (DEFRA) by BRASS at Cardiff University, involving an in-depth survey both of current corporate social responsibility (CSR) reporting in the UK nanotechnologies industry, and of attitudes to particular stakeholder issues within the industry. The article analyses the results to give an account of the nature of corporate social performance (CSP) within the industry, together with the particular model of CSR operating therein (‘do no harm’ versus ‘positive social force’). It is argued that the nature of emerging technologies requires businesses to adopt particular visions of CSR in order to address stakeholder issues, and that the nanotechnologies industry presents specific obstacles and opportunities in this regard.
Keywords: Innovation; Risk; Uncertainty; Stakeholder engagement; CSP; CSR; Nanotechnology